Severe hypertriglyceridemia secondary to venlafaxine use in an older adult on dialysis -case report - Hsiang-Wen Lin; Cory A. Simonavice; Chiung-Ray Lu; Wen-Ling Lin; Po-Lun Wu; Che-Yi Chou; Chun-Hui Liao; Hsieh-Yuan Lane (BMC, 2017)
Abstract Background Although the prescribing information for Venlafaxine extended release includes a discussion about possible increases in total cholesterol and triglycerides (TG) seen in healthier adult patients during premarketing clinical trials, no post-marketing studies or case reports, that discuss the effects of venlafaxine on TG in elderly patients with chronic kidney disease. Case presentation We report a 71 year-old male patient with end-stage renal disease on hemodialysis, with a history of coronary artery disease, mild hyperlipidemia, and hypertension. This patient twice demonstrated the severe rises in triglycerides while taking the antidepressant, i.e., venlafaxine, and discontinuing the long-term use of fenofirate. The adverse drug reaction sub-committee at the hospital rated the second event as a "probable reaction" using the Naranjo nomogram, accordingly. Conclusions This case demonstrates the risk of changes in lipid profiles while taking venlafaxine and receiving on and off fenofibrate therapy in the older adult patient with chronic kidney disease and under hemodialysis. Regular monitoring for lipid changes after starting venlafaxine is strongly advised for patients with existing risk factors.